Creation and the world of science : the re-shaping of belief - Peacocke, A. R. (Arthur Robert) (Oxford University Press, 2004)
A.R. Peacocke's "Creation and the World of Science", an expanded version of his 1978 Bampton Lectures, was widely recognized as a key work on the relation of the sciences to religion, in general, and Christian theology in particular. It has long been seen as a formative contribution to the wide-ranging investigations, which now, internationally, constitute this intensely active field. This new reprinting contains the original and influential text and also contains a new supplement containing key references to the literature of recent years as well as indicating the author's current position on central themes. It constitutes an essential reference and starting point for the contemporary discussion of key issues in the dialogue between the sciences and theology
Originally published: Oxford : Clarendon Press; New York : Oxford University Press, 1979.
Keywords: Creation.; Religion and science.; Religion and Science; Création.; Religion et sciences.; creating (artistic activity); creation (doctrinal concept); RELIGION -- Christianity -- General.; RELIGION -- Christian Life -- Social Issues.; Creation; Religion and science; Schepping.; Geloof en wetenschap.; Electronic book.